Learning across geographic space: Pro-market reforms, multinationalization strategy, and profitability - Dau, Luis Alfonso (Journal of International Business Studies, 2013)
Building on economic geography and knowledge-based theory, I argue that pro-market reforms augment the profitability of firms by increasing their competitiveness and market knowledge. However, I propose that this effect is greater for firms that operate internationally, firms that operate in more advanced markets, and firms that become multinationals before reforms are implemented. This is because such firms acquire market knowledge abroad that they can use when responding to reforms at home, giving them a head-start advantage over other local firms. The analyses of a panel of the largest 500 Latin American companies from 1989 to 2008 provide support for these arguments.